Wacana Hadis Feminis terhadap Profesi Jurnalis Perempuan (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2021)
The role of women in the public sphere, in some societies is still constructed in a limited dimension, where women are still at a level below men and are considered taboo in some professions.  Journalism as a profession that is seen as a masculine profession, because it requires skills, abilities and energy that is difficult for women to do.  This assumption undermines the role of women and the validity of the information they convey.  In contrast, Islam as a religion that supports gender equality for women, provides equal opportunities for men and women to engage in activities in the public sphere, including in the field of journalism.  To examine the existence of this support, it will be studied using a qualitative method with a feminist analysis approach aimed at the traditions which are understood as the prophet's support for the journalist profession.  Based on the search for hadiths, it was found some information related to the role of women in the field of journalism, as evidenced by a number of hadiths of the prophet that explain the participation of women in conveying information